Examining the links between sense of belonging, conflict resolution skills, emotional intelligence, and life satisfaction in Chinese universities - Yun Liu; Bin Zeng; Liang Chang (BMC Psychology)
Abstract Background This study explores the interrelationships among emotional intelligence, conflict resolution skills, sense of belonging, and life satisfaction among university students in Mainland China. Drawing from Baumeister and Leary’s theory of belongingness, this research examines both the direct and indirect effects of emotional intelligence and conflict resolution skills on life satisfaction, with sense of belonging serving as a mediator. Methods A sample of 369 university students completed validated self-report measures assessing emotional intelligence, conflict resolution skills, sense of belonging, and life satisfaction during the 2023–2024 academic year. Structural equation modeling was used to test the hypothesized relationships. Results The results revealed significant positive direct effects of both emotional intelligence (β = 0.32, p <.01) and conflict resolution skills (β = 0.27, p <.01) on life satisfaction. Additionally, sense of belonging significantly mediated the effects of both emotional intelligence (β = 0.19, p <.01) and conflict resolution skills (β = 0.18, p <.01) on life satisfaction, underscoring the importance of social integration in student well-being. Conclusion The findings suggest that students with higher emotional intelligence and effective conflict resolution skills experience greater life satisfaction, partly due to an enhanced sense of belonging. These results have significant theoretical and practical implications for educational institutions aiming to foster student well-being by advocating for interventions that promote emotional intelligence, conflict resolution skills, and a supportive, inclusive campus environment.